ISOLATION AND GENOTYPING OF PORCINE RESPIRATORY AND REPRODUCTIVE SYNDROME VIRUS ON PIG FARMS IN LIMA AND AREQUIPA, PERU - Ramírez V., Mercy (2013)
The aim of this study was to isolate and genotyping the Porcine Respiratory and Reproductive Syndrome Virus (PRRSV) strain in pig farms in Lima and Arequipa, Peru. Seropositive pig farms to PRRSV were identified by ELISA test. Blood samples were collected from weaned pigs from positive pig farms in Lima (A=44, B=20; C=16) and Arequipa (D=32, E=92). The serum samples (n=204) were processed in 51 pools of 4 samples each for virus isolation using Porcine Alveolar Macrophage (PAM) cell line. The genome of the virus isolated was identified by Reverse Transcription-nested Polimerase Chain Reaction (RT-nPCR). The complementary DNA (cDNA) of genotype 1 and 2 of PRRSV vaccine strains were used as positive controls and cDNA of equine viral arteritis virus, classical swine fever virus and PAM cells as negative controls in the RT-nPCR. Three blind passages in PAM cell line with each of the 51 pool were done before searching PRRSV antigen by Immunofluorescence test. The 19.6% (10/51) of samples were positive to viral antigen by IF. The 70% (7/10) of the isolated strains had no cytopathic effect. Eight out of ten positive samples were confirmed as PRRSV using RT-nPCR test and 1 of the 41 negative samples was positive to PRRSV by RT-nPCR. The 17.6% (9/51) of isolated were positives to PRRSV using primers that recognize the common genomic sequence to genotype 1 and 2 of PRRSV. All the PRRSV strains confirmed by RT-nPCR test belonged to genotype 1. This is the first evidence of genotype 1-European of PRRSV in pig farms in Peru.